The THE INFLUENCE OF CONTINUITY OF CARE (COC) TO THE INCREASING OF COGNITIVE, AFFECTIVE AND PSYCHOMOTOR ASPECTS OF MIDWIFERY CARE TO STUDENTS OF MIDWIFERY STUDY PROGRAM - Lasiyati Yuswo Yani; Ariu Dewi Yanti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Education should be able to form graduate competencies in accordance with community needs. The quality of midwives in Indonesia is still low, this is indicated by the passing of the competency test which tends to be volatile (RistekDikti, 2016). During this time the learning aspects are given fragmented and separate. Learning models are needed in accordance with the needs of the community, integrating all aspects related to community values and are dynamic according to the needs of the community. The purpose of this study was to find the effect of CoC learning methods on improving cognitive, affective and psychomotor midwifery students. This study used